(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2016)
The Commission set up by the Presidency of the Federal Senate to draw up a preliminary draft of the Code of Civil Procedure suggested the creation of a separate Title to regulate the this initiative was approved by the Senate with the aim of eliminating academic discussions about the nature of the court system. This initiative, approved by the Senate, was aimed at eliminating academic discussions about the nature of the provisional anticipation of the effects of injunctive relief, currently provided for in art. 273 of the Code. Alongside this measure, there is the possibility of the judge granting the party, also on a provisional basis, injunctive relief, regulated by articles 797 et seq. of the procedural statute. According to the criterion adopted by the Brazilian legislator, both of these types of injunctive relief are characterized by not being the final protection granted to the holder of a particular claim brought before the courts. In the cases in which they are authorized, these types of relief, always preceded by summary cognition, are simply intended to ensure the practical effectiveness of definitive relief, which is preceded, at least in principle, by exhaustive cognition and a judgment of certainty. We can then point to the criteria taken into account by the legislator to classify the remedies which ensure the usefulness of the final outcome of the process. They are informed by summary cognition, which is capable of revealing the truth of the case.